2020
DOI: 10.3791/60651
|View full text |Cite
|
Sign up to set email alerts
|

Using the Chicken Chorioallantoic Membrane In Vivo Model to Study Gynecological and Urological Cancers

Abstract: Mouse models are the benchmark tests for in vivo cancer studies. However, cost, time, and ethical considerations have led to calls for alternative in vivo cancer models. The chicken chorioallantoic membrane (CAM) model provides an inexpensive, rapid alternative that permits direct visualization of tumor development and is suitable for in vivo imaging. As such, we sought to develop an optimized protocol for engrafting gynecological and urological tumors into this model, which we present here. Approximately 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The method we used was similar to already published HET-CAM models [17,83,[91][92][93][94]. Fertilized chicken eggs (LSL Rhein-Main Geflügelvermehrungsbetriebe GmbH & Co.KG, Dieburg, Germany) were defined upon start of incubation on embryo development day 0 (EDD0).…”
Section: Het-cam Modelmentioning
confidence: 99%
“…The method we used was similar to already published HET-CAM models [17,83,[91][92][93][94]. Fertilized chicken eggs (LSL Rhein-Main Geflügelvermehrungsbetriebe GmbH & Co.KG, Dieburg, Germany) were defined upon start of incubation on embryo development day 0 (EDD0).…”
Section: Het-cam Modelmentioning
confidence: 99%
“…To do so, we established RCC xenografts in the chorioallantoic membrane (CAM) model [ 33 , 34 ]. Our experience has shown that the CAM model is an efficient, time-saving in vivo model, especially for establishing human RCC xenografts [ 35 , 36 ]. Furthermore, it faithfully recapitulates the metastatic behaviors of the mouse model [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…To assess RCC xenografts metastasis in vivo, we established the CAM model with fertilized duck eggs as our previously published protocols [ 35 , 36 , 37 , 38 ]. Freshly laid fertilized duck eggs were incubated in a MultiQuip incubator (MULTIQUIP, E2, AISTRAL, Australia) at 37 °C with 60% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Establishment of CAM tumor xenografts and their analyses were performed as previously described 34,56,57 . Intrarenal implantation of 1x10^6 total RC or AC tumor cells was performed as previously described 29,36 .…”
Section: Cell Proliferation Assaymentioning
confidence: 99%